(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2015)
The method for localization of isolated direct contour lines based on form-factor is proposed in this paper. The essence of this method consists in comparison to unit of value of form-factor –the relations of the size of the contour line (distance between end points) to its length (number of the forming contour pixels). It is found that the proposed method provides a gain in speed of allocating direct contour lines in 4 times in comparison with the method of LSD (Line Segment Detector) and in 14.8 times in comparison with the method based on the Hough transform.The effective method of normalization of the contour line on thickness on the basis of the analysis of orientation of the connected pixels is proposed in this paper. This method is specially developed for deleting excess pixels of a dedicated line.Also developed algorithm of normalization of contour lines on thickness promotes the best calculation of a form-factor.